Association between Number of Formed Embryos, Embryo Morphology and Clinical Pregnancy Rate after Intracytoplasmic Sperm Injection - Luz, Caroline Mantovani da; Giorgi, Vanessa Silvestre Innocenti; Coelho Neto, Marcela Alencar; Martins, Wellington de Paula; Ferriani, Rui Alberto; Navarro, Paula Andrea (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2016)
Introduction Infertility has a high prevalence in the general population, affecting ∼ 5 to 15% of couples in reproductive age. The assisted reproduction techniques (ART) include in vitro manipulation of gametes and embryos and are an important treatment indicated to these couples. It is well accepted that the implantation rate is positively influenced by the morphology of transferred embryos. However, we question if, apart from the assessment of embryo morphology, the number of produced embryos per cycle is also related to pregnancy rates in the first fresh transfer cycle.Purpose To evaluate the clinical pregnancy rate according to the number of formed embryos and the transfer of top quality embryos (TQEs).Methods In a retrospective cohort study, between January 2011 and December 2012, we evaluated women who underwent intracytoplasmic sperm injection (ICSI), aged < 40 years, and with at least 1 formed embryo fresh transferred in cleavage stage. These women were stratified into 3 groups according to the number of formed embryos (1 embryo, 2–3 and ≥ 4 embryos). Each group was divided into 2 subgroups according to the presence or not of at least 1 transferred TQE (1 with TQE; 1 without TQE; 2–3 with TQE, 2–3 without TQE; ≥ 4 with TQE; ≥ 4 without TQE). The clinical pregnancy rates were compared in each subgroup based on the presence or absence of at least one transferred TQE.Results During the study period, 636 women had at least one embryo to be transferred in the first fresh cycle (17.8% had 1 formed embryo [32.7% with TQE versus 67.3% without TQE], 42.1% of women had 2–3 formed embryos [55.6% with TQE versus 44.4% without TQE], and 40.1% of patients had ≥ 4 formed embryos [73.7% with TQE versus 26.3% without TQE]). The clinical pregnancy rate was significantly higher in the subgroup with ≥ 4 formed embryos with at least 1 transfered TQE (45.2%) compared with the subgroup without TQE (28.4%).Conclusions Having at least two available embryos and at least one TQE for embryo transfer are predictors of the pregnancy rates.
Keywords: number of embryos; morphological evaluation; embryo quality; clinical pregnancy; ICSI